Catalytic upgrading of renewable levulinic acid to ethyl levulinate biodiesel using dodecatungstophosphoric acid supported on desilicated H-ZSM-5 as catalyst - Nandiwale, Kakasaheb Y.; Sonar, Shilpa K.; Niphadkar, Prashant S.; Joshi, Praphulla N.; Deshpande, Shilpa S.; Patil, Vilas S.; Bokade, Vijay V. (Applied Catalysis A-General, 2013)
Levulinic acid (LA) is considered as a renewable platform chemical and can be used for the synthesis of variety of important fuels and chemicals. In particular, its esterification with ethanol produces ethyl levulinate (EL) would be green process, as it can be used as diesel miscible biofuel (DMB), preventing global warming by decreasing atmospheric CO2. This study explores the use of modified H-ZSM-5 by desilication viz.; DH-ZSM-5 and dodecatungstophosphoric acid (DTPA) loaded on DH-ZSM-5 for esterification of LA with ethanol aiming to EL. Different degree of desilication of H-ZSM-5 was performed by using aq. NaOH (0.2-1.5 M) at 338 K for 30 min and then DTPA was loaded on these desilicated H-ZSM-5 (DH-ZSM-5) support. H-ZSM-5, DH-ZSM-5 and DTPA on these DH-ZSM-5 samples were characterized by powder x-ray diffraction (XRD), N-2 adsorption-desorption, pyridine chemisorbed IR spectroscopy, Temperature Programmed Ammonia Desorption (TPAD). The increase in conversion of levulinic acid was observed from 28% to 94% with increase of DTPA loading from 0% to 15%. The increased LA conversion may be due to increase in total acidity from 43.14% to 84.31%. The use of DH-ZSM-5 as support for deposition of DTPA may be reported for the first time. The present work also extended to optimize process parameters such as DTPA loading on DH-ZSM-5, catalyst to LA ratio, LA to ethanol molar ratio, speed of agitation, particle size reaction temperature and catalyst reusability. Kinetic study based on pseudo-homogeneous (P-H) model is also presented. The experimental results follow second order kinetics. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: desilicated H-ZSM-5; DTPA on desilicated H-ZSM-5; Esterification; ethyl levulinate; levulinic acid

Enhanced dual-effect of adsorption and photodegradation of SiO2 embedded TiO2 hybrid catalyst for improved decolourization of methylene blue - Sonar, Shilpa K.; Wagh, Reshma V.; Niphadkar, Prashant S.; Joshi, Praphulla N.; Deshpande, Shilpa S.; Awate, Shobhana V. (Water Air and Soil Pollution, 2013)
Dual-effects of adsorption and photodegradation over titania, silica embedded titania, silica and commercial Degussa P-25 samples were studied for the decolourization of methylene blue in aqueous medium. Silica embedded titania and silica were prepared using inexpensive polymeric version of ethyl silicate as a source of silica. Catalysts were characterized by X-ray diffraction, scanning electron microscopy, UV-Vis spectroscopy and low temperature (77 K) nitrogen adsorption measurements. Among all the catalysts, silica embedded titania has exhibited faster decolourization of methylene blue solution on account of the enhancement of adsorption followed by degradation. An amount of the catalyst and the initial dye concentration of MB solution were found to influence the decolourization activity. Compared to titania catalyst, silica embedded titania and Degussa P-25 have shown the red shift in their UV-Vis spectrum. The experimental data of the reaction fitted well to the pseudo first order kinetic model. In present studies, the adsorption mechanism for the decolourization of MB solution was found to be applicable for an intra particle diffusion model.
Keywords: Adsorption; kinetic model; Methylene blue; Photodegradation; Silica embedded titania

Preparation and characterization of porous fly ash/NiFe2O4 composite: promising adsorbent for the removal of congo red dye from aqueous solution - Sonar, Shilpa K.; Niphadkar, Prashant S.; Mayadevi, S.; Joshi, Praphulla N. (Materials Chemistry and Physics, 2014)
A series of fly ash/NiFe2O4 composites were prepared using fly ash and aqueous solutions of Ni, Fe nitrate salts and NaOH by co-precipitation followed by calcination method. The % mass ratio of fly ash: NiFe2O4 was varied in the range of 0:100 to 100:0. Samples were characterized by powder XRD, SEM, FTIR and N-2 adsorption-desorption measurements. These samples were further evaluated for their adsorptive performance in removal of Congo red (CR) dye from an aqueous solution. In all the composites, spinel nickel ferrite phase was found to be capable to get anchored with the fly ash surface and exhibited more crystalline nature as compared to pure NiFe2O4 phase. The BET surface area and porous character of the composite were found to increase with the decrease in the contribution of the fly ash, reach to maximum and then decreases on further decrease in fly ash. The composite having % mass ratio of fly ash: NiFe2O4 = 50:50 exhibited maximum CR adsorption from the aqueous solution on account of the higher BET surface area, more porous character, favorable condition for diffusion of dye molecules and combined effect of chemisorption and physisorption. Under optimum conditions, it has shown the recyclability with adsorption capacity of the magnitude 23.33 mg g(-1), which is much higher than individual fly ash, NiFe2O4 and other composites. The sorption data provided good fit with pseudo-second order kinetic model. The analyses of the adsorption data indicated that, the Langmuir model provides better correlation with the experimental data. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Adsorption; Composite material; Electron microscopy (SEM); Inorganic compounds; powder diffraction; Precipitation

Hierarchical K/LTL zeolites: synthesis by alkali treatment, characterization and catalytic performance in knoevenagel condensation reaction - Tangale, Nilesh P.; Sonar, Shilpa K.; Niphadkar, Prashant S.; Joshi, Praphulla N. (Journal of Industrial and Engineering Chemistry, 2016)
The hierarchical K/LTL zeolites prepared by post-synthesis modification with aqueous 1.5 M KOH solution by varying alkali volume to K/LTL zeolite (10-70 ml/g) ratios, were examined in Knoevenagel condensation. The physico-chemical properties of the catalysts were thoroughly evaluated by PXRD, ICP, CO2-TPD, XPS, N-2 adsorption/desorption and Si-29 and Al-22 MAS-NMR. Among all the samples, hierarchical K/LTL prepared by treating K/LTL with 50 ml aqueous 1.5 M KOH solution per gram of K/LTL displayed about 1.5 fold higher catalytic activity as compared to parent K/LTL, presumably because of combined effect of enhanced basicity and molecular diffusion through pore channels. (C)2016 The Korean Society of Industrial and Engineering Chemistry. Published by Elsevier B.V. All rights reserved.
Keywords: Basicity; Hierarchical zeolite; K/LTL; Knoevenagel condensation; Micro-mesoporous composite